2020
DOI: 10.1186/s12935-020-1105-6
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH5-mediated m6A demethylation of lncRNA PVT1 plays an oncogenic role in osteosarcoma

Abstract: Background: Osteosarcoma (OS) is one of the most common malignant bone tumors. Plasmacytoma variant translocation 1 (PVT1) is a well-known oncogenic long noncoding RNA (lncRNA). However, to date, the regulatory mechanism of PVT1 upregulation in OS remains unknown.Methods: qRT-PCR was carried out to test the expression level of PVT1 and ALKBH5. RNA immunoprecipitation (RIP) and RNA pull-down assays were performed to detect the interaction of PVT1 with ALKBH5 and YTHDF2. Methylated RNA immune-precipitation (MeRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(138 citation statements)
references
References 23 publications
1
137
0
Order By: Relevance
“…As for other cancers, ALKBH5 was significantly downregulated in clear cell renal cell carcinoma (ccRCC) compared to normal tissue [45]. It was also affirmed that ALKBH5 took a great part in contributing to osteosarcoma tumorigenesis [40]. ALKBH5, directly regulated by human RNA helicase DDX3, decreased m6A methylation in FOXM1 and NANOG nascent transcript and contributed to chemoresistance of oral squamous cell carcinoma(OSCC) [46].…”
Section: Alkbh5 In Other Cancersmentioning
confidence: 91%
See 2 more Smart Citations
“…As for other cancers, ALKBH5 was significantly downregulated in clear cell renal cell carcinoma (ccRCC) compared to normal tissue [45]. It was also affirmed that ALKBH5 took a great part in contributing to osteosarcoma tumorigenesis [40]. ALKBH5, directly regulated by human RNA helicase DDX3, decreased m6A methylation in FOXM1 and NANOG nascent transcript and contributed to chemoresistance of oral squamous cell carcinoma(OSCC) [46].…”
Section: Alkbh5 In Other Cancersmentioning
confidence: 91%
“…Moreover, ALKBH5 demethylated lncRNA KCNK15-AS1, which was downregulated in pancreatic cancer tissues compared with the normal tissues, thus elevating pancreatic cancer motility, including migration and invasion [26]. In addition, ALKBH5 suppressed the degradation of lncRNA plasmacytoma variant translocation 1 (PVT1), which was up-regulated in osteosarcoma tissues and cells, thus promoting the osteosarcoma cell proliferation in vitro and tumor growth in vivo through inhibiting the binding of m6A reader YTHDF2 in PVT1 [40]. ALKBH5 decreased the level of lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1), which was overexpressed in gastric cancer cells and tissue, and took a great part in the invasion and metastasis of gastric cancer [19].…”
Section: Regulatory Mechanisms Of Alkbh5mentioning
confidence: 99%
See 1 more Smart Citation
“…The aberrantly expressed genes were associated with pluripotency regulation of the OSCs ( Wang J. et al, 2019 ). Further, it has been shown that lncRNA plasmacytoma variant translocation 1 (PVT1) transcript was upregulated because of m 6 A methylation decrease mediated by ALKBH5, which reduced the binding of reader protein YTHDF2 in PVT1, subsequently lessening the degradation of PVT1 and promoting tumorigenesis of OS ( Chen et al, 2020 ). METTL3 was found localizing in both cytoplasm and nucleus of OS cells, which is also on the map of OS modulation.…”
Section: Roles Of M 6 a In Musculoskeletal Disordementioning
confidence: 99%
“…For instance, METTL3-mediated m 6 A modification led to LINC00958 upregulation through stabilizing its RNA transcript, and LINC00968 sponged miR-3619-5p to upregulate HDGF expression thereby facilitating the lipogenesis and progression of hepatocellular carcinoma (HCC) [ 27 ]. Another investigation revealed that m 6 A demethylase ALKBH5 could suppress the degradation of lncRNA PVT1, and its overexpression promoted osteosarcoma cell proliferation in vitro and tumor growth in vivo [ 28 ]. Similar phenomenon could also be observed in GC-related lncRNAs with m 6 A [ 29 ].…”
Section: Discussionmentioning
confidence: 99%